The Influence of Information Technology Mastery and Work Motivation on the Teacher Performance - Nisak, Khoirotun; Ratumanan, Tanwey Gerson; Rahabav, Patris (AT-TA'LIM, 2023)
The aims of this research is to determine the effect of information technology mastery and work motivation on teacher performance. This research was conducted at SMA Negeri 6 Seram Bagian Timur and SMA Negeri 9 Seram Timur, involving 41 teachers. The results of this research explained that the data description for the variable mastery of information technology, obtained as many as 12 teachers (29.27%) had very high mastery of information technology, 25 teachers (60.98%) had high mastery of information technology and 4 teachers (9.75%) has moderate mastery of information technology. The description of the data for the work motivation variable in this research was that 16 teachers (39.02%) had very high work motivation, 16 teachers (39.02%) had high work motivation, and as many as 9 teachers (21.96%) had work motivation. In the middle category. Furthermore, for the teacher performance, it was found that 13 teachers (31.71%) had very high teacher performance, 22 teachers (53.66%) had high teacher performance, and 6 teachers (14.63%) had moderate performance. Based on the results of the analysis of the three hypotheses, the following conclusions can be obtained: (1) The mastery of information technology has no positive and significant influence on the teacher’s performance due to some factors; (2) There is a significant effect of work motivation on teacher performance. This is evidenced by Fcount = 27.750 Ftable = 3.24 with a coefficient of determination (R Square) of 0.416; (3) There is a significant influence of information technology mastery and work motivation together on the teacher’s performance. This is evidenced from Fcount = 15.650 Ftable = 3.24 with a coefficient of determination (R Square) value is 0.452